Communication Strategy of Wali Nanggroe in Safeguarding Peace in Aceh - Bustami; Lahmuddin; Zainun; Hasrat Efendi Samosir (Yayasan Darussalam Bengkulu, 2026)
The objective of this study is to analyze the communication strategies implemented by the Wali Nanggroe in safeguarding peace, governing Aceh, fostering media relations, as well as identifying the challenges encountered. This research employed a descriptive qualitative approach, aiming to systematically and comprehensively portray a social phenomenon within its natural context. Data were collected through interviews, observations, and documentation. The findings reveal that the communication strategy of the Wali Nanggroe in safeguarding peace in Aceh is carried out through two main models: high-level communication with national and international figures to ensure the implementation of the peace agreement or the Helsinki MoU and the Law on the Governing of Aceh (LoGA), as well as direct communication with the community, former combatants, traditional leaders, and religious scholars to gather aspirations, foster collective awareness, and detect potential conflicts at an early stage. In addition, a cultural approach is employed through the empowerment of traditional institutions in Aceh.